The Analysis of Trade Circumvention, Threats and Risk to the Duties and Functions of the Directorate General of Customs and Excise (DJBC) Indonesia - Tagara Primadista; Arthur Josias Simon Runturambi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One of the threats from international trade is trade circumvention (TC) schemes with the aim of avoiding antidumping rules or restrictions on the number of incoming goods (quotas). This paper tries to explore the phenomenon of TC in Indonesia through a qualitative approach. Using the literature study method by studying the literature and related documents, this paper analyzes the threats and risks of TC to Indonesia from the perspective of law enforcement intelligence. The results of this study indicate that Indonesia's main threat is being dragged into a situation as a third country or destination country in the TC cycle. The risks faced are not only detrimental from an economic perspective related to trade and state revenues, but also Indonesia's bilateral relations with other countries. Meanwhile, in terms of law enforcement intelligence, prevention of TC in Indonesia requires appropriate laws or regulations to make it easier for relevant agencies or institutions to take action against TC practices. Data integration between related agencies or institutions is also very decisive in preventing TC practices in the future.